2021
DOI: 10.26848/rbgf.v14.4.p1880-1897
|View full text |Cite
|
Sign up to set email alerts
|

Identificação das causas climáticas dos eventos extremos e dos impactos dos ENOS Canônico e Modoki nas macrorregiões de Alagoas

Abstract: Anomalies of sea surface temperature that occur in some regions of the Equatorial Pacific Ocean are being studied because their cause different impacts and originate in different ways, are the ENOS, Modoki and Canonical. The objective of this work is to identify the climatic causes of the extreme events that occurred in the macro-regions of Alagoas, and at the same time, to compare the effects of ENOS Canonical and Modoki and their classes on the macro-regions of Alagoas. The daily precipitation data for 21 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…In all 3 years evaluated in the study (1983, 1998 and 2015), the highest values were recorded in the northern part of the East Alagoas region, resembling the results obtained by Da Silva et al (2021), which showed positive SPI values for the region. Regardless of the Very Strong El Niño events, the region stood out with the highest rainfall totals, indicating the influence of other synoptic and mesoscale meteorological systems, such as EWD, breeze circulation, the position of the ITCZ, and SST anomalies near the NEB coast, which contribute to increased rainfall totals in this region (Lyra et al, 2014, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In all 3 years evaluated in the study (1983, 1998 and 2015), the highest values were recorded in the northern part of the East Alagoas region, resembling the results obtained by Da Silva et al (2021), which showed positive SPI values for the region. Regardless of the Very Strong El Niño events, the region stood out with the highest rainfall totals, indicating the influence of other synoptic and mesoscale meteorological systems, such as EWD, breeze circulation, the position of the ITCZ, and SST anomalies near the NEB coast, which contribute to increased rainfall totals in this region (Lyra et al, 2014, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…These variations are directly associated with the influence of sea surface temperature variability in the tropical South Atlantic, in contrast to Pacific tropical conditions (Kayano and Andreoli, 2006). Recently, some authors have identified the association of various simultaneous and multiscale systems/phenomena, for example, Oliveira‐Júnior et al (2021a, 2021b), Santos Rocha et al (2022), Silva et al (2020) and Da Silva et al (2021), mainly in the ENEB, with an influence on the occurrence of extreme rainfall and drought.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the effects of modes of climate variability could be examined and related to temporal trends in rainfall patterns. Trends detected mostly in months of transition from the dry and rainy season (March, April and September), between 1995 and 2000, coincide with changes in the PDO phase from warm to cold in 1999 (NASA, 2022) and the very strong El Niño event of 1997/98, one of the strongest of the 20th century (Ballester et al, 2016; Costa et al, 2020; Da Silva et al, 2021; Oliveira‐Júnior et al, 2021).…”
Section: Discussionmentioning
confidence: 94%